2022
DOI: 10.7150/ijms.76664
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA ncRuPAR regulates gastric cancer cell proliferation and apoptosis via phosphoinositide 3-kinase/protein kinase B signaling

Abstract: Objective: To determine the effect and mechanism of the long non-coding RNA (lncRNA) ncRuPAR (non-protein coding RNA, upstream of coagulation factor II thrombin receptor [F2R]/protease-activated receptor-1 [PAR-1]) in human gastric cancer. Methods: HGC-27-ncRuPAR overexpression and MGC-803-ncRuPAR-RNAi knockdown gastric cancer cell lines were established. We assessed the effect of ncRuPAR on cell proliferation, apoptosis, migration, and invasion using Cell Counting Kit 8, flow cytometry, scratch and transwell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…PAR‐1 could promote pancreatic cancer cells' migration, invasion ability, and EMT (H. Liu et al., 2020). Inhibiting PAR‐1 can further inhibit proliferation and promote cell death of gastric cancer cells (Xu et al., 2022). Same as these results, our study found knockdown PAR‐1 could promote inflammatory factors and apoptotic of SUDHL2, inhibited proliferation, migration, and invasion of SUDHL2, and its results were the same when DLBCL cells were hypoxic.…”
Section: Discussionmentioning
confidence: 99%
“…PAR‐1 could promote pancreatic cancer cells' migration, invasion ability, and EMT (H. Liu et al., 2020). Inhibiting PAR‐1 can further inhibit proliferation and promote cell death of gastric cancer cells (Xu et al., 2022). Same as these results, our study found knockdown PAR‐1 could promote inflammatory factors and apoptotic of SUDHL2, inhibited proliferation, migration, and invasion of SUDHL2, and its results were the same when DLBCL cells were hypoxic.…”
Section: Discussionmentioning
confidence: 99%
“…Crucially, non‐coding RNA‐mediated epigenetic modifications play an important role in the process of GC cell apoptosis, including long non‐coding RNA (lncRNA) (Xiao et al, 2022), micro‐RNA (miR) (Kipkeeva et al, 2020), and circular RNA (circRNA) (Li, Yang, & Xu, 2020c). For instance, lncRNA‐ncRuPAR was shown to promote apoptosis in human GC cells by inhibiting PAR‐1, PI3K/Akt signaling and cyclin D1 (Xu, Yu, et al, 2022b). MiR‐874‐3p, sponged by LINC00922, was found to inhibit GC progression by targeting glycerophosphodiester phosphodiesterase domain containing 5 (GDPD5) and promoting apoptosis (Zhang, Dai, et al, 2022e).…”
Section: Insights Into Rcds In Gcmentioning
confidence: 99%
“…F11-AS1 regulates the expression of PTEN through competitive binding with miR-3146 , thereby inhibiting the progression of LIHC ( 22 ). Another CRL, ncRuPAR (non-protein coding RNA, upstream of coagulation factor II thrombin receptor [F2R]/protease-activated receptor-1 [PAR-1]), can inhibit tumor cell proliferation and promote apoptosis of human gastric cancer cells by inhibiting PAR-1, PI3K/Akt signaling, and cyclin D1, and its downregulation can promote angiogenesis, invasion, metastasis, and progression ( 23 , 24 ). However, it is not clear whether CRLs have a regulatory effect on the occurrence and development of CRC.…”
Section: Introductionmentioning
confidence: 99%